Achieving Equitable Education Missing Education Data and the SDG 4 Data Regime NORRAG Series on International Education and Development - Delprato, Marcos (Edward Elgar Publishing, 2024)
This is an open access title available under the terms of a CC BY-NC-ND 4.0 License. It is free to read, download and share on Elgaronline.com. Achieving Equitable Education argues that critical gaps in education data are hampering the achievement of one of the UN's Sustainable Development Goals: "inclusive and equitable quality education...for all". This book critically explores education data gaps across regions, themes and levels of education, highlighting key relationships and disconnects between national, regional and global data needs.